Serum S100 Protein Is a Reliable Predictor of Brain Injury After Out-of-Hospital Cardiac Arrest: A Cohort Study - Kleissner, Martin; Sramko, Marek; Kohoutek, Jan; Kautzner, Josef; Kettner, Jiri (Frontiers in Cardiovascular Medicine, 2021)
Purpose: To evaluate serum S100 protein at hospital admission and after 48 h in early neuroprognostication of comatose survivors of out-of-hospital cardiac arrest (OHCA). Methods: The study included 48 consecutive patients after OHCA, who survived for at least 72 hours after the event. The patients were divided based on their best cerebral performance category (CPC) achieved over a 30-day follow-up period: favorable neurological outcome (CPC 1-2) vs. unfavorable neurological outcome (CPC 3-4). Predictors of an unfavorable neurological outcome were identified by multivariable regression analysis. Analysis of the receiver operating characteristic (ROC) curve was used to determine the cut-off value for S100, having a 0% false-positive prediction rate. Results: Of the 48 patients, 30 (63%) had a favorable and 18 (38%) had an unfavorable neurological outcome. Eleven patients (23%) died over the 30-day follow-up. Increased S100 levels at 48 hours after OHCA, but not the baseline S100 levels, were independently associated with unfavorable neurological outcome, with an area under the ROC curve of 0.85 (confidence interval 0.74 – 0.96). A 48-hour S100 value ≥ 0.37 µg/L had a specificity of 100% and sensitivity of 39% in predicting an unfavorable 30-day neurological outcome. Conclusion: This study showed that S100 values assessed 48 hours after an OHCA could independently predict an unfavorable neurological outcome at 30 days.